Phospholipase activity of acyloxyacyl hydrolase induces IL‐22‐producing CD1a‐autoreactive T cells in individuals with psoriasis. Issue 3 (10th January 2022) - Singh, Randeep; Chen, Yi‐Ling; Ng, Soo Weei; Cain, David; Etherington, Rachel; Hardman, Clare; Ogg, Graham
Abstract: Psoriasis is a chronic inflammatory skin disease characterized by Th17 responses. Recent evidence has identified Langerhans cells to have a key role in disease pathogenesis, with constitutive high expression of CD1a and capacity to present lipid antigens to T cells. Phospholipase A2 enzymes generate neolipid antigens for recognition by CD1a‐reactive T cells; however, the broader enzymatic pathways of CD1a lipid ligand generation have not been thoroughly investigated. In this study, we used immunofluorescence of skin and ELISpot analyses of CD1a‐reactive T cells to investigate the role of the lipase acyloxyacyl hydrolase (AOAH) in CD1a ligand generation with relevance to the pathogenesis of psoriasis. We found that the PLA2 activity of rAOAH leads to the activation of circulating CD1a auto‐reactive T cells, leading to the production of IFN‐γ and IL‐22. Circulating AOAH‐responsive CD1a‐reactive T cells from patients with psoriasis showed elevated IL‐22 production. We observed that AOAH is highly expressed in psoriatic lesions compared to healthy skin. Overall, these data present a role for AOAH in generating antigens that activate circulating lipid‐specific CD1a‐restricted T cells and, thus, contribute to psoriatic inflammation. These findings suggest that inhibition of PLA2 activity of AOAH may have therapeutic potential for individuals with psoriasis. Abstract : Acyloxyacyl hydrolase (AOAH), a lipase with PLA2 activity is highly expressed in lesional psoriatic skin. PLA2 activity of AOAH was found to activate CD1a‐reactive T cells. Individuals with psoriasis had elevated IL‐22 production by AOAH‐responsive circulating CD1a‐reactive T cells.